2012
DOI: 10.1118/1.4764908
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of the slice sensitivity profiles in breast tomosynthesis and breast CT

Abstract: Purpose: This study experimentally evaluated the slice sensitivity profile (SSP) and its relationship between acquisition angle, object size, and cone angle. The sensitivity profile metric was used to characterize a breast tomosynthesis system's resolution in the z-axis. The SSP was also measured on a prototype breast computed tomography (bCT) system. Methods: The SSP was measured using brass disks placed within adipose tissue-equivalent breast phantoms. The digital tomosynthesis system (Selenia Dimensions, Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(59 reference statements)
1
17
0
Order By: Relevance
“…The ability of a tomographic system to separate the slices is referred to as slice sensitivity profile (SSP). In digital breast tomosynthesis, SSP worsens with increasing object diameter and improves when the arc span is increased, whereas breast CT provides a constant SSP . That study also showed that for the 15 degree arc span used by a digital breast tomosynthesis system, the effective slice thickness is 8 mm even for a very small object, and was 0.5 mm for a breast CT system with voxel pitch of 0.23 mm.…”
Section: The Developing Role Of Breast Ctmentioning
confidence: 65%
“…The ability of a tomographic system to separate the slices is referred to as slice sensitivity profile (SSP). In digital breast tomosynthesis, SSP worsens with increasing object diameter and improves when the arc span is increased, whereas breast CT provides a constant SSP . That study also showed that for the 15 degree arc span used by a digital breast tomosynthesis system, the effective slice thickness is 8 mm even for a very small object, and was 0.5 mm for a breast CT system with voxel pitch of 0.23 mm.…”
Section: The Developing Role Of Breast Ctmentioning
confidence: 65%
“…1] has been proposed as a method of assessing the resolution and characterizing reconstruction artifacts in breast tomosynthesis. [1][2][3] The full-width halfmaximum (FWHM) of a Gaussian fit to the SSP has been proposed as measurement to summarize the SSP for the purposes of QC tracking and equipment characterization. 1 Smaller FWHM values correspond to better resolution in the z-direction (perpendicular to the x-ray detector) and less out of plane artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the thickness of the breast under standard mammography is that of the entire breast, averaging about 5 cm for the typical woman. Although tomosynthesis breast images are produced every millimeter in depth on some systems, the effective slice thickness of these images is approximately 10–20 mm thick, depending upon the size of the contrast-forming objects (Nosratieh et al, 2012). …”
Section: Introductionmentioning
confidence: 99%